2016
DOI: 10.1007/s11356-016-6115-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal performance in planted and unplanted horizontal subsurface flow constructed wetlands treating different influent COD/N ratios

Abstract: Microcosm horizontal subsurface flow constructed wetlands (HSSFCWs) were used to examine the impacts of vegetation on nitrogen dynamics treating different influent COD/N ratios (1:1, 4:1, and 8:1). An increase in the COD/N ratio led to increased reductions in NO3 and total inorganic nitrogen (TIN) in planted and unplanted wetlands, but diminished removal of NH4. The HSSFCW planted with Canna indica L. exhibited a significant reduction in NH4 compared to the unplanted system, particularly in the active root zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Ye and Li [56] concluded that the entire denitrification of 1.0 g nitrate nitrogen into nitrogen gas needed 2.86 g BOD. Meanwhile, a variety of studies have shown that macrophytes can effectively enhance the carbon content, thus, aiding nitrogen removal in the CWs [7,25,57]. On the one hand, plant root exudates can provide available organic compounds to heterotrophic bacteria [8], on the other, plant litter can release various dissolved organic matters including sugars, amino acids, and volatile fatty acids [48,58].…”
Section: Discussionmentioning
confidence: 99%
“…Ye and Li [56] concluded that the entire denitrification of 1.0 g nitrate nitrogen into nitrogen gas needed 2.86 g BOD. Meanwhile, a variety of studies have shown that macrophytes can effectively enhance the carbon content, thus, aiding nitrogen removal in the CWs [7,25,57]. On the one hand, plant root exudates can provide available organic compounds to heterotrophic bacteria [8], on the other, plant litter can release various dissolved organic matters including sugars, amino acids, and volatile fatty acids [48,58].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of organic matter supply hindered the process of denitrification and further led to the accumulation of NO 3 − -N in the presence of aeration. Wang et al [30] also revealed that the carbon source was insufficient when COD/N ratios were less than 4. Subsequently, the removal percentages of TN increased to 99.5% at a COD/N ratio of 9.3 and then slightly decreased to 97.3% in HSSF-CW with IA.…”
Section: Nh 4 + -N and Tn Removal In Hssf-cws Under Different Influenmentioning
confidence: 99%
“…Plant materials are mainly added to sewage to serve as external carbon sources and biofilm carriers (Wang et al, 2016; Yang et al, 2019). However, this also leads to many problems.…”
Section: Introductionmentioning
confidence: 99%